Purification and characterization of an alkalistable phytase produced by Rhizopus microsporus var. microsporus in submerged fermentation - de Oliveira Ornela, Pedro Henrique [UNESP]; Souza Guimarães, Luis Henrique (Elsevier, 2019)
The filamentous fungus Rhizopus microsporus var. microsporus produces an alkaline phytase in submerged fermentation. This alkaline phytase was purified 83-fold with 1.9% protein yield. The molecular mass of the glycoprotein was estimated in 12% SDS-PAGE as 55 kDa and 63 kDa as revealed by gel filtration, indicating a monomeric structure for the enzyme. The alkaline phytase was optimally active at 65 °C and pH 9.5, with a half-life (T1/2) of 280 min at 50 °C. At 80 °C, the enzyme maintained 87% of its initial activity for 280 min. The phytase activity was characterized as alkalistable and this activity was stimulated when maintained at pH 8.0 and 9.0. It was inhibited mainly by KH2PO4, β-mercaptoethanol, EDTA, HgCl2, and urea. The alkaline phytase activity was also inhibited by detergents (Triton X-100, Tween 20, and SDS) and solvents (acetone, acetonitrile, ethanol, isopropanol, methanol, and n-butanol). The alkaline phytase showed a preference for sodium phytate as substrate (100%), followed by ATP (27.9%) and p-NPP (11.5%). The Km value for sodium phytate was 0.413 mmol L−1. This study represents the first description of the purification and characterization of a fungal alkaline phytase.
Keywords: Alkaline phytase; Enzyme characterization; Phytic acid; Rhizopus